Clinical Outcomes of Retrograde Double J Stenting of the Ureter in Benign Obstructed Etiology Under Local Anesthesia - a Prospective Observational Study - Tepukiel Zaphu; R. Manikandan; Ketan Mehra; Uma Kant Dutt (Dr. Annil Mahajan, 2022)
Background: To study the clinical outcome of retrograde double J stent insertion of the ureter in benign etiologies, using rigid cystoscope under LA along with factors leading to failure and its complications. Material and Methods: A prospective observational study was conducted from December 2015 to June 2017 and a total of 140 patients were studied after institute ethics committee approval. Retrograde D J stent insertion is done under LA with fluoroscopic guidance. The demographic data and other parameters were studied to find out the success of the DJ stent along with factors for failure of the procedure and its complications. Results: Calculous diseases were the most common cause followed by diabetic papillary necrosis. The success of stenting was 90.3%. of patients. The cooperation of patients tolerating the procedure under LA was related to the success of the procedure and showed a significant association (p=0.026). Failure of contrast going up on retrograde pyelography was the main reason for the failed procedure and is significant (p=0.000). UWT on NCCT didn't have any relation with the failed procedure (p=1). Conclusion: The DJ stenting of the ureter with a rigid cystoscope under LA (spongiosal block in males) is safe and feasible with a high success rate. The ureteral parameters especially the UWT do not predict the success or failure of the procedure pre-operatively. The failure of contrast going up on RGP is significant (p=0.000) with failure of DJ stent.